Second take at love - Crespo, Nina, 1967- (Harlequin special edition, 2023)
"She's no trespasser...but causing trouble just the same. Hoping to get away from the hustle of Hollywood, producer Holland Ainsley finds the perfect subject for her new project. Except the old Maryland farmhouse comes with widower Myles Alexander. His goal is to fix up the place and sell it, not have a beloved memory become some documentary. Holland's vision may prove more enticing than Myles's battered heart imagines. Is his heart also ready for a reality check on happiness?"--